Methodological Guidelines for the Deontological Adaptation of Future Teachers in the Education Process - Khanat, Kasenov; Gulsara, Urazbayeva; Madina, Tusupbekova; Roza, Zhusupova; Gulmira, Tugelbayeva (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The methodological guidelines of deontological adaptation of future teachers in the education process are considered: the main vectors of adaptation processes to learning, the mechanisms of professional semantic generation, and adaptation algorithms. This article presents the research of a pedagogical experience of teacher training on the subject of Deontology adaptation, a curricular unit which is part of the education degrees taught at Eurasian National University named after Gumilev (Kazakhstan). The foundation of the curricular unit and its characteristics are presented, as well as the analysis of the students' evaluation of its teaching effects as perceived by them. The data analysis, based on some contents of a portfolio, shows a considerable positive perception of those effects. The purpose of the research is to determine and substantiate the study's methodology and develop the organizational and methodological support for the deontological training of bachelor's education as the basis for the formation of their deontological competence and personal and professional development.